Tuning of Redox Energy of Transition-Metal Ions through the Utilization of Interlayer Potentials in Layered Perovskites: Development of a Titanium-Based Superior HER Catalyst in an Acidic Medium - Jaiswal S.; Mondal R.; Kushwaha V.; Gupta A.; Singh P. (My University, 2025)
Efficient electrolysis of water is important for green hydrogen production using renewable energy sources, which requires efficient electrocatalysts having active sites for the hydrogen evolution reaction (HER) to reduce the overpotential and energy consumption. The most efficient HER catalysts are Pt-, Ru-, and Ir-based noble metals, which catalyze the HER with near-zero overpotential. Electrocatalysis utilizes a redox process of the active cation in the framework; the host cations accept/donate electrons for each such conversion reaction or catalytic activity. The relative position of these redox energies with respect to the Fermi level and controlling their variations in different oxides are important for designing novel electrocatalysts and electrodes for electrochemical conversion devices. The utilization of interlayer potential to tune the relative redox energies of the Ti(IV)/Ti(III) redox couples in layered K- and Gd-doped NaYTiO4, Na1-xKxY1-xGdxTiO4 (x ≤ 0.2), was envisaged here to develop a superior HER electrocatalyst. Polycrystalline sodium yttrium titanate (NaYTiO4) has been synthesized by the sol-gel method and presented as an efficient catalyst for the HER for the very first time. Electrochemical studies reveal superior HER activity; the NaYTiO4 activity is not only better than that of TiO2 due to distorted (elongated) octahedral TiO6 present in NaYTiO4 but also superior or at least equivalent to that of most of the oxide electrocatalysts studied for the HER. Electrochemical tests reveal good HER performance of our synthesized electrocatalyst with an overpotential of 148 mV and a Tafel slope of 102 mV/dec with good stability for 24 h. Furthermore, due to the increase in strength of the interlayer dipolar electric field (interlayer potential), NaY0.8Gd0.2TiO4 (overpotential: 106 mV; Tafel slope: 90 mV/dec) showed superior activity to that of NaYTiO4. Utilization of the interlayer potential and strategy for altering the internal electric field (interlayer potential) in layered materials to tune the redox energies of active redox couples and superior electron transfer accelerated by the internal electric field or interlayer potential is presented in the article that can be further utilized to develop superior electrocatalysts and electronic materials. © 2023 American Chemical Society.